SHOCKING CASES, POLICE NEWS AND LOCAL JOURNALISTIC PRACTICES IN SMALL TOWNS OF THE BUENOS AIRES PROVINCE. THE ANTONIA CASE IN AYACUCHO, 2011 - Galar, Santiago (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2017)
The article proposes to analyze from a sociological perspective the local journalistic practice around the constitution of shocking cases in small towns of Buenos Aires province. The research focus attention to trouble practices of the local journalists in the city of Ayacucho using as a reference a death that happened in the town in 2011 that was constituted as a national shocking case: the Antonia case. With these objectives we interviewed local journalists, developed participant observations in their work environments, andanalyzed sources of local, provincial and national press. The analysis of the coverage of the Antonia case allows to advance in the characterization of practices, categorizations and ratings shared by local journalists organized around the production of police news, a territory rarely explored by the social sciences in our country. The revealing power of the case is expressed particularly in two tensions produced in its configuration process as an event. On the one hand, a tension derived from the presence of national press journalists whose practices questioned local journalists. On the other hand, a tension between the daily routines of local journalists and the extraordinary practices demands for a case that generated attention of local and extra local audiences. Regarding their experiences in the case, crossed by these and other tensions, the local journalists identified possibilities and restrictions that link to the exercise of the profession in the context of a small city.